Cold sintering molybdenum copper material and preparation method and application thereof
Through cold sintering technology, the problems of low density and uneven composition of molybdenum copper heat sink material are solved under the synergistic effect of anhydrous ethanol and glacial acetic acid solution, and the molybdenum copper material with high density, low thermal expansion coefficient and high thermal conductivity are achieved. Preparation, simplifies the process and reduces costs, is suitable for mass production applications of small-size molybdenum copper alloys.
Patent Information
- Application Number
- CN202411556657.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-27
AI Technical Summary
The existing preparation methods for molybdenum copper heat sink materials have problems such as complex equipment, high cost, low product density, non-uniform distribution of components and difficult to adjust the size, and are especially not suitable for the preparation of small-sized molybdenum copper alloys.
Using cold sintering technology, ball-milling molybdenum copper alloy raw materials in anhydrous ethanol, glacial acetic acid solution is added for low temperature heating and high pressure treatment, and the grain structure rearrangement and diffusion are promoted through dissolution and precipitation mechanism, combined with annealing to eliminate internal stress, and high-induced ejaculation is prepared. Molybdenum copper material with density and low thermal expansion coefficient.
It realizes the densification of molybdenum-copper alloy, improves thermal conductivity and composition uniformity, simplifies equipment and processes, reduces energy consumption, and is suitable for the mass production of small-sized molybdenum-copper alloys.
Smart Images

Figure CN119187569A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat sink materials, and in particular to a cold-sintered molybdenum-copper material and a preparation method and application thereof. Background Art
[0002] Heat sink materials are used to transfer the heat generated by power electronic devices and integrated circuits in a timely manner, so heat sink materials are required to have high thermal conductivity and a thermal expansion coefficient that matches the chip. Molybdenum-copper alloy is a pseudo-alloy composite material formed by two immiscible metals. It combines the advantages of high hardness, high strength, and low thermal expansion coefficient of pure molybdenum and high thermal conductivity and high electrical conductivity of copper. At the same time, the thermal conductivity and thermal expansion coefficient can be designed by adjusting the Mo / Cu composition ratio. Therefore, molybdenum-copper alloy is the most widely used electronic packaging heat sink material.
[0003] At present, the production methods of molybdenum-copper heat sink materials are mainly melt infiltration and liquid phase sintering. The melt infiltration method is to first prepare a molybdenum skeleton, cover the copper sheet, sinter at a temperature slightly higher than the melting point of copper, and use capillary force to make the copper liquid penetrate into the molybdenum skeleton, and then cool it to form a molybdenum-copper alloy. The liquid phase sintering method mainly involves mixing two metal powders, adding an activator, adding a binder, pressing and forming, and then debinding and sintering.
[0004] However, the molybdenum-copper alloy prepared by the existing technology is limited by the difficulties such as the immiscible solid solubility of molybdenum and copper and the large difference in melting points. The molybdenum-copper alloy prepared by the melt infiltration method still needs to be rolled after melt infiltration to achieve a low expansion coefficient molybdenum-copper alloy. Therefore, the melt infiltration method is not suitable for the preparation of small-sized molybdenum-copper alloys.
[0005] When using the liquid phase sintering method, the introduction of an activator will reduce the thermal and electrical conductivity of the alloy, and the mixed powder will make it difficult to densify the alloy due to the segregation of material components. Therefore, the method to improve the molybdenum-copper alloy is usually to increase the sintering temperature or extend the sintering time. However, excessively high sintering temperatures will lead to grain growth. In addition, high-temperature sintering will inevitably bring about prominent energy consumption problems. At present, the main low-temperature sintering process methods include spark plasma sintering technology and microwave sintering technology, but the equipment used is complex and costly, and cannot be applied in mass production.
[0006] Based on this, it is of great significance to provide a method for preparing a molybdenum-copper material that is suitable for small-sized molybdenum-copper alloys and has a simple preparation method, low cost and is suitable for mass production. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems existing in the prior art in the preparation of molybdenum-copper materials, such as complex equipment, high cost, low relative density of the product, non-uniform distribution of components, and difficulty in adjusting size.
[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a cold sintered molybdenum-copper material, the method comprising the following steps:
[0009] (1) ball milling a molybdenum-copper alloy raw material in the presence of anhydrous ethanol to obtain a Mo-Cu mixed powder;
[0010] (2) mixing the Mo-Cu mixed powder with a glacial acetic acid solution, and then heating the mixture for a first time without applying pressure, and when the temperature rises to 90-100° C., heat preservation for a first time for 8-15 minutes to obtain a mixture I;
[0011] (3) The mixture I is heated for a second time at a pressure of 350-500 MPa, and when the temperature rises to 300-400° C., it is kept warm for a second time for 55-120 min, and then annealed after cooling to obtain a cold-sintered molybdenum-copper material.
[0012] The second aspect of the present invention provides a cold-sintered molybdenum-copper material prepared by the method described in the first aspect.
[0013] The third aspect of the present invention provides the application of the cold-sintered molybdenum-copper material described in the second aspect in electronic packaging.
[0014] Compared with the prior art, the method provided by the present invention has at least the following beneficial effects:
[0015] (1) The present invention adopts cold sintering technology, adds glacial acetic acid solution, combines the synergistic effect of low temperature and high pressure, and uses the dissolution precipitation mechanism to transport particles in the high chemical potential area, effectively promotes grain structure rearrangement and diffusion, and quickly realizes the sintering densification of molybdenum-copper alloy. After annealing to eliminate internal stress, the thermal expansion coefficient of the material is finally reduced, and the thermal conductivity is improved. The density problem of molybdenum-copper alloy is successfully solved, and the product size is small and the composition is uniform;
[0016] (2) Compared with the traditional preparation process, the cold sintering method for preparing molybdenum-copper heat sink materials requires simple equipment, the process is streamlined and optimized, and can be put into mass production to better achieve the goal of energy conservation and emission reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a schematic structural diagram of a sintering device used in a preferred embodiment of the present invention;
[0018] Figure 2 It is the X-ray diffraction pattern of the cold-sintered molybdenum-copper material prepared by the preferred embodiment of the present invention. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] As mentioned above, the first aspect of the present invention provides a method for preparing a cold sintered molybdenum-copper material, the method comprising the following steps:
[0021] (1) ball milling a molybdenum-copper alloy raw material in the presence of anhydrous ethanol to obtain a Mo-Cu mixed powder;
[0022] (2) mixing the Mo-Cu mixed powder with a glacial acetic acid solution, and then heating the mixture for a first time without applying pressure, and when the temperature rises to 90-100° C., heat preservation for a first time for 8-15 minutes to obtain a mixture I;
[0023] (3) The mixture I is heated for a second time at a pressure of 350-500 MPa, and when the temperature rises to 300-400° C., it is kept warm for a second time for 55-120 min, and then annealed after cooling to obtain a cold-sintered molybdenum-copper material.
[0024] According to a preferred embodiment, in step (1), the average volume diameter of the Mo-Cu mixed powder is 3-8 μm. Studies have found that in this preferred embodiment, the uniformity of the molybdenum-copper material can be improved, and the sintering activity of Mo-Cu can be ultimately improved, achieving low-temperature sintering densification.
[0025] Preferably, in step (1), the molybdenum-copper alloy raw material consists of metal molybdenum powder and metal copper powder, wherein the weight ratio of the metal molybdenum powder to the metal copper powder is 1-4:1.
[0026] Preferably, the average volume diameter of the metal molybdenum powder is 2-10 μm.
[0027] Preferably, the metal copper powder has an average volume diameter of 3-12 μm.
[0028] Preferably, in step (1), the ball milling is performed using a horizontal ball mill, the ball milling medium is tungsten alloy balls, and the material-ball mass ratio is 1:1.
[0029] Preferably, in step (1), the ball milling is carried out in an argon atmosphere and at least the following conditions are met: a rotation speed of 100-250 r / min, a temperature of 60-80° C., and a time of 6-24 h.
[0030] Preferably, the method of the present invention further comprises, in step (1), drying the Mo-Cu mixed powder obtained after the ball milling at 60-120° C. for 1-3 h, and then applying it to the operation in step (2).
[0031] According to a preferred embodiment, in step (2), the weight ratio of the Mo-Cu mixed powder to the glacial acetic acid solution is 1-5:1; wherein,
[0032] The concentration of the glacial acetic acid solution is 2-10 mol / L. Studies have found that under this preferred condition, glacial acetic acid is conducive to forming an intermediate phase and uniformly wetting the molybdenum-copper composite material, and forming a liquid film on the surface of the particles. This liquid film causes local dissolution of the particle tip, and acts as a lubricant to accelerate the rearrangement and slip of the particles. During the heating process under constant pressure, the intermediate phase continues to evaporate, and the solution gradually reaches an oversaturated state, causing the dissolved molybdenum-copper powder to precipitate in the form of precipitation. The chemical potential of the pore area is lower than that of the particle contact area, and the dissolved atomic clusters or ions will migrate to the lower chemical potential area for precipitation, thereby reducing the surface energy and gradually realizing the low-temperature sintering densification of the molybdenum-copper composite material.
[0033] Preferably, the rates of the first heating, the second heating and the cooling are independently 3-10° C. / min.
[0034] Preferably, in step (3), the annealing is performed in an argon or hydrogen atmosphere and at least satisfies the following conditions: a temperature of 800-950° C. and a time of 1-2 h.
[0035] Preferably, the method of the present invention further comprises, in step (3), before performing the annealing, heating the system to 800-950° C. at a rate of 4-10° C. / min, and then performing the annealing.
[0036] According to a preferred embodiment, the operations of step (2) and step (3) in the present invention are Figure 1 The sintering equipment shown in the figure is carried out, specifically including:
[0037] (1) In the presence of anhydrous ethanol, a molybdenum-copper alloy raw material is ball-milled in a horizontal ball mill to obtain a Mo-Cu mixed powder;
[0038] (2) Mixing the Mo-Cu mixed powder with glacial acetic acid solution to obtain Mo x Cu (1-x) Then the Mo x Cu (1-x) Transfer to Figure 1In the mold of the sintering device shown, the heating plate is heated without pressure to perform a first temperature increase, and when the temperature rises to 90-100° C., a first heat preservation is performed for 8-15 minutes to obtain a mixture I;
[0039] (3) applying uniaxial pressure to the mold so that the pressure in the mold reaches 350-500 MPa, heating the heating plate to heat the mixture I for a second time, and when the temperature rises to 300-400° C., performing a second heat preservation for 55-120 min, cooling and annealing to obtain a cold sintered molybdenum-copper material.
[0040] As mentioned above, the second aspect of the present invention provides a cold-sintered molybdenum-copper material prepared by the method described in the first aspect.
[0041] As mentioned above, the third aspect of the present invention provides the application of the cold-sintered molybdenum-copper material described in the second aspect in electronic packaging.
[0042] The present invention is described in detail below by way of examples. Unless otherwise specified, the raw materials used are all common commercially available products.
[0043] Metal molybdenum powder: average volume diameter is 5μm;
[0044] Metal copper powder: The average volume diameter is 4 μm.
[0045] Example 1
[0046] This embodiment is used to illustrate that the method for preparing the cold sintered molybdenum-copper material provided by the present invention is carried out according to the following steps:
[0047] (1) In an argon atmosphere and in the presence of anhydrous ethanol, a molybdenum-copper alloy raw material (the weight ratio of metal molybdenum powder to metal copper powder is 2.3:1) is ball-milled in a horizontal ball mill (the ball milling medium is tungsten alloy balls, and the mass ratio of the balls is 1:1) to obtain a Mo-Cu mixed powder with an average volume diameter of 3 μm;
[0048] Among them, the speed is 200r / min, the temperature is 60℃, and the time is 20h;
[0049] (2) drying the Mo-Cu mixed powder at 80° C. for 2 h, and then mixing it with a glacial acetic acid solution (with a concentration of 4 mol / L) at a weight ratio of 1.1:1 to obtain Mo x Cu (1-x) , and then the Mo x Cu (1-x) Transfer to Figure 1In the mold with an inner diameter of 15 mm in the sintering equipment shown, a heating plate is heated without pressure to perform a first temperature increase (heating rate of 5° C. / min), and when the temperature rises to 100° C., a first heat preservation is performed for 10 min to obtain a mixture I;
[0050] (3) applying uniaxial pressure to the mold so that the pressure in the mold reaches 500 MPa, heating the heating plate to heat the mixture I for a second time (heating rate is 5°C / min), and when the temperature rises to 300°C, a second heat preservation is performed for 60 minutes, and after cooling (cooling rate is 5°C / min), hydrogen is introduced, and then heated to 900°C at a rate of 10°C / min for annealing for 2 hours to obtain a cold sintered molybdenum-copper material, named P1;
[0051] Figure 2 The X-ray diffraction pattern (XRD pattern) of P1 is shown. It can be seen from the figure that the diffraction peaks and their corresponding angles can determine that the phase composition of P1 is Mo 70 Cu 30 .
[0052] Example 2
[0053] This embodiment is carried out in a similar manner to that of embodiment 1, except that the condition parameters of step (3) are different, specifically including:
[0054] (3) The mixture I was heated for a second time at a pressure of 350 MPa, and when the temperature reached 310° C., it was kept warm for a second time for 55 min. After cooling, it was annealed to obtain a cold-sintered molybdenum-copper material, named P2.
[0055] Example 3
[0056] This embodiment is carried out in a similar manner to that of Embodiment 1, except that in step (2), the weight ratio of the Mo-Cu mixed powder to the glacial acetic acid solution is 0.8:1, and the concentration of the glacial acetic acid solution used is 1.5 mol / L:
[0057] Finally, a cold-sintered molybdenum-copper material was obtained, named P3.
[0058] Example 4
[0059] This example is carried out in a similar manner to Example 1, except that the parameters of the ball milling are controlled so that the average volume diameter of the Mo-Cu mixed powder obtained after ball milling in step (1) is 10 μmL:
[0060] Finally, a cold-sintered molybdenum-copper material was obtained, named P4.
[0061] Comparative Example 1
[0062] This comparative example is carried out in a similar manner to Example 1, except that the first heating and first heat preservation operations in step (2) are not performed, specifically comprising:
[0063] S1. In an argon atmosphere and in the presence of anhydrous ethanol, a molybdenum-copper alloy raw material (the weight ratio of metal molybdenum powder to metal copper powder is 2.3:1) is ball-milled in a horizontal ball mill (the ball-milling medium is tungsten alloy balls, and the mass ratio of the balls is 1:1) to obtain a Mo-Cu mixed powder with an average volume diameter of 3 μm;
[0064] Among them, the speed is 200r / min, the temperature is 60℃, and the time is 20h;
[0065] S2, drying the Mo-Cu mixed powder at 80°C for 2h, and then mixing it with glacial acetic acid solution at a weight ratio of 1.1:1 to obtain Mo x Cu (1-x) , and then the Mo x Cu (1-x) Transfer to Figure 1 In the mold with an inner diameter of 15 mm in the sintering equipment shown, the second heating is directly carried out under a pressure of 500 MPa. When the temperature rises to 300°C, a second heat preservation is carried out for 60 minutes. After cooling, annealing is carried out to obtain a sintered molybdenum-copper material, named DP1.
[0066] Comparative Example 2
[0067] This comparative example is carried out in a similar manner to Example 1, except that in step (2), the temperature after the first heating is 200° C., and then the first heat preservation is carried out for 10 minutes to obtain a mixture I which is applied to the operation in step (3);
[0068] Finally, a sintered molybdenum-copper material was obtained, named DP2.
[0069] Comparative Example 3
[0070] The traditional melt infiltration method is used for preparation, which includes:
[0071] SS1. Take the same mass of metal molybdenum powder as in Example 1, obtain a molybdenum blank by pressure molding, and then carry out a degumming process from room temperature (28° C.) to a maximum temperature of 600° C. for a total of 18 hours to discharge moisture and organic matter in the compact;
[0072] SS2, then carry out pre-sintering in the high temperature stage, the highest temperature is 1150°C, the highest temperature holding time is 2h, and the pre-sintered molybdenum billet is obtained;
[0073] SS3, and finally copper infiltration is carried out, that is, in a reducing atmosphere, the temperature is kept at 1250°C for 2 hours, and finally, a sintered molybdenum-copper material is obtained, named DP3.
[0074] Test Example 1
[0075] The cold sintered molybdenum-copper material and the sintered molybdenum-copper material prepared in the above examples were subjected to relevant tests on thermal conductivity, including:
[0076] Density: measured by Archimedes displacement method;
[0077] Relative density: the ratio of the actual mass density of a material to its theoretical density;
[0078] Average linear thermal expansion coefficient (hereinafter referred to as thermal expansion coefficient) under room temperature to 400°C conditions: refer to the standard "QBT 1321-1991 Method for Determination of Average Linear Thermal Expansion Coefficient of Ceramic Materials";
[0079] Thermal conductivity: Measure the thermal conductivity with reference to "Measurement of thermal diffusion coefficient by flash method according to GB / T 22588-2008", then measure the material density with the water displacement method, calculate the corresponding theoretical specific heat capacity, and finally calculate the thermal conductivity of the material with the formula;
[0080] Please see Table 1 for the results.
[0081] Table 1
[0082] project P1 P2 P3 P4 DP1 DP2 DP3 <![CDATA[Density (g / cm 3 )]]> 9.8 9.83 9.77 9.78 9.70 9.72 9.75 Relative density 99.5% 99.8% 99.2% 99.3% 98.2% 98.7% 98.9% Thermal expansion coefficient (ppm / K) 6.8 6.8 6.90 6.88 7.15 7.10 7.12 Thermal conductivity (W / (m·k)) 187 192 185 183 175 177 180
[0083] It can be seen from the above results that the method provided by the present invention adjusts the sintering process and utilizes a low-temperature cold sintering method to prepare a molybdenum-copper alloy with high density, low thermal expansion coefficient, high thermal conductivity, and flexible size. In addition, the material utilization rate is high, the process is simple, the material sintering temperature is greatly reduced, the sintering time is shortened, which is beneficial to carbon emission reduction and has good market application prospects.
[0084] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing cold sintered molybdenum-copper material, characterized in that: The method comprises the following steps: (1) ball milling a molybdenum-copper alloy raw material in the presence of anhydrous ethanol to obtain a Mo-Cu mixed powder; (2) mixing the Mo-Cu mixed powder with a glacial acetic acid solution, and then heating the mixture for a first time without applying pressure, and when the temperature rises to 90-100° C., heat preservation for a first time for 8-15 minutes to obtain a mixture I; (3) The mixture I is heated for a second time at a pressure of 350-500 MPa, and when the temperature rises to 300-400° C., it is kept warm for a second time for 55-120 min, and then annealed after cooling to obtain a cold-sintered molybdenum-copper material.
2. The method according to claim 1, characterized in that In step (1), the average volume diameter of the Mo-Cu mixed powder is 3-8 μm.
3. The method according to claim 1 or 2, characterized in that: In step (1), the molybdenum-copper alloy raw material is composed of metal molybdenum powder and metal copper powder, wherein the weight ratio of the metal molybdenum powder to the metal copper powder is 1-4:
1.
4. The method according to claim 1 or 2, characterized in that: In step (1), the ball milling is carried out in an argon atmosphere and at least meets the following conditions: a rotation speed of 100-250 r / min, a temperature of 60-80° C., and a time of 6-24 h.
5. The method according to claim 1 or 2, characterized in that: In step (2), the weight ratio of the Mo-Cu mixed powder to the glacial acetic acid solution is 1-5:1; wherein, The concentration of the glacial acetic acid solution is 2-10 mol / L.
6. The method according to claim 1 or 2, characterized in that: The rates of the first heating, the second heating and the cooling are each independently 3-10° C. / min.
7. The method according to claim 1 or 2, characterized in that: In step (3), the annealing is performed in an argon or hydrogen atmosphere and at least satisfies the following conditions: a temperature of 800-950° C. and a time of 1-2 h.
8. The method according to claim 1 or 2, characterized in that: The method further comprises, in step (3), before performing the annealing, heating the system to 800-950° C. at a rate of 4-10° C. / min, and then performing the annealing.
9. A cold-sintered molybdenum-copper material prepared by the method described in any one of claims 1 to 8.
10. Application of the cold-sintered molybdenum-copper material according to claim 9 in electronic packaging.
